Evaluation of the Inhibitory Activity of Tea Tree Leaves Essential Oils Against Cryptococcus neoformans and Candida tropicalis - Mohammed, Sajad H.; Abed, Ibrahim J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
Tea tree oil, extracted from the leaves of1Melaleuca alternifolia, is `known for 1its antibacterial and antioxidant properties. This study aimed to investigate its chemical composition, antifungal activity against Candida tropicalis and Cryptococcus neoformans, and free radical1 scavenging capacity. Evaluating the inhibitory activity of tea tree essential1 oil1. Essential oil was obtained via steam 1distillation from air-dried 1leaves. Chemical constituents were analyzed using Gas chromatography-mass spectrum analysis. Antifungal1 activity was assessed1 by agar dilution assays at concentrations of 200–2,000 µg/ml. Antioxidant1 activity was determined using the DPPH assay within the 12.5–200 μL range. GC–MS analysis identified terpinen-4-ol1(18.3%), γ-terpinene (11.2%), α-pinene (7.2%), terpinolene (4.0%), sabinene (3.2%), and camphene (1.1%) as major components. Complete inhibition of both yeast species occurred at 500 ppm, establishing the minimum inhibitory concentration. Determination of antioxidant activity by 2,2-Diphenyl-1-picrylhydrazyl radical (DPPH) free radical scavenging assay revealed a dose-dependent increase in radical scavenging, with 50% inhibition achieved at approximately 22 μL of oil. Tea tree oil rich in terpinen-4-ol1 exhibits moderate antifungal activity and notable antioxidant potential. These findings support its potential1 use as a natural1 preservative or adjunct therapeutic agent. Further work is required1to optimize formulations and evaluate safety for clinical and industrial applications